Cognitive symptoms associated with antipsychotic course experience in residual schizophrenia - Safonov, D. (Journal of Education, Health and Sport, 2021)
Urgency. The cognitive symptoms of schizophrenia are recognized either as a part of a negative complex of symptomatic, where cognitive malfunction seem to be the secondary complication of emotional and motivational dysregulation; or as a separate group of schizophrenia manifestations that constitutes a massive part of a residual condition. Aim – to evaluate the cognitive functioning and analyze its violation levels in association with antipsychotic course experience in patients with residual schizophrenia. Results. The assessment of cognitive functions was established by direct testing in clinical setting. Education in years varied from 9 to 16, mean 11,27±2,12 in the population under study. The basic level of cognitive impairment was established: verbal memory test result was 31,6±11,6; digit sequencing test result was 13,4±5,7; token motor task test result was 40,1±18,3; verbal fluency test result was 41,2±10,7; symbol coding test result was 30,6±13,1; tower of london test result was 12,2±4,5. Some correlations were found: for chlorpromazine we can assume minor negative impact on token motor task (r= -0,22) and verbal fluency test (r= -0,27) results; for haloperidol we can assume more pronounced but still minor impact on token motor task (r= -0,22), verbal fluency test (r= -0,27), verbal memory test (r= -0,28) and tower of London test (r= -0,20) results; for trifluoperazine we can see minor negative impact on verbal fluency test (r= -0,26); for clozapine we can’t find any representative correlations with cognitive tests; chlorprothixene as we can assume have minor negative impact on verbal memory test (r= -0,32) result, but minor positive – on tower of London test (r= 0,21) result; for risperidone also assume minor positive impact on sequence coding test (r= 0,25), but other tests in battery show no significant correlations; for zuclopenthixol we can assume minor negative impact on token motor task (r= -0,22) and verbal fluency test (r= -0,31) results.